Cross-border mobility in European countries: associations between cross-border worker status and health outcomes - Lucas Nonnenmacher; Michèle Baumann; Etienne le Bihan; Philippe Askenazy; Louis Chauvel (BMC, 2021)
Abstract Background Mobility of workers living in one country and working in a different country has increased in the European Union. Exposed to commuting factors, cross-border workers (CBWs) constitute a potential high-risk population. But the relationships between health and commuting abroad are under-documented. Our aims were to: (1) measure the prevalence of the perceived health status and the physical health outcomes (activity limitation, chronic diseases, disability and no leisure activities), (2) analyse their associations with commuting status as well as (3) with income and health index among CBWs. Methods Based on the 'Enquête Emploi', the French cross-sectional survey segment of the European Labour Force Survey (EU LFS), the population was composed of 2,546,802 workers. Inclusion criteria for the samples were aged between 20 and 60 years and living in the French cross-border departments of Germany, Belgium, Switzerland and Luxembourg. The Health Index is an additional measure obtained with five health variables. A logistic model was used to estimate the odds ratios of each group of CBWs, taking non-cross border workers (NCBWs) as the reference group, controlling by demographic background and labour status variables. Results A sample of 22,828 observations (2456 CBWs vs. 20,372 NCBWs) was retained. The CBW status is negatively associated with chronic diseases and disability. A marginal improvement of the health index is correlated with a wage premium for both NCBWs and CBWs. Commuters to Luxembourg have the best health outcomes, whereas commuters to Germany the worst. Conclusion CBWs are healthier and have more income. Interpretations suggest (1) a healthy cross-border phenomenon steming from a social selection and a positive association between income and the health index is confirmed; (2) the existence of major health disparities among CBWs; and (3) the rejection of the spillover phenomenon assumption for CBWs. The newly founded European Labour Authority (ELA) should take into account health policies as a promising way to support the cross-border mobility within the European Union.